2020
DOI: 10.1002/cjoc.202000432
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Mannich‐Type Reaction Enabled by Efficient Dienolization of α,β‐Unsaturated Pyrazoleamides†

Abstract: Asymmetric catalysis | Vinylogous reaction | Pyrazoleamide | Copper catalyst | Dienolization (E)-α,β-Unsaturated pyrazoleamides undergo facile dienolization to furnish copper(I)-(1Z,3Z)-dienolates as the major in the presence of a copper(I)-(R)-DTBM-SEGPHOS catalyst and Et 3 N, which react with aldimines to afford syn-vinylogous products as the major diastereoisomers in high regio-and enantioselectivities. In some cases, the diastereoselectivity is low, possibly due to the low ratio of copper(I)-(1Z,3Z)-dienol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…Bisphosphines bearing a ferrocene-core, such as ( R )-( S )-JOSIPHOS and ( R , R P )-TANIAPHOS, were acceptable ligands due to high yields and high regio-, and high enantioselectivities even though the diastereoselectivity was moderate (entries 9 and 10). The ligand screening of commercially available bisphosphines revealed again that ( R )-DTBM-SEGPHOS was a privileged ligand in the copper­(I)-catalyzed asymmetric vinylogous and alkynylogous reactions. ,,,, Screening of organic bases identified TMG as the best choice as up to >99% yield was obtained (entry 11). The loading of copper­(I)-( R )-DTBM-SEGPHOS and TMG was successfully reduced to 2 mol % but with moderate yield (entry 12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bisphosphines bearing a ferrocene-core, such as ( R )-( S )-JOSIPHOS and ( R , R P )-TANIAPHOS, were acceptable ligands due to high yields and high regio-, and high enantioselectivities even though the diastereoselectivity was moderate (entries 9 and 10). The ligand screening of commercially available bisphosphines revealed again that ( R )-DTBM-SEGPHOS was a privileged ligand in the copper­(I)-catalyzed asymmetric vinylogous and alkynylogous reactions. ,,,, Screening of organic bases identified TMG as the best choice as up to >99% yield was obtained (entry 11). The loading of copper­(I)-( R )-DTBM-SEGPHOS and TMG was successfully reduced to 2 mol % but with moderate yield (entry 12).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it was revealed that pyrazoleamides of α,β-unsaturated acids underwent facile dienolization in the presence of Et 3 N and the copper­(I)-bisphosphine complex, which enabled a direct vinylogous Mannich-type reaction. , Allylcopper­(I) species were proposed as the operating nucleophiles in direct vinylogous Mannich-type reactions. Based on these interesting findings, it was envisioned that pyrazoleamides of acetylenic acids could be used as efficient pronucleophiles, which would undergo facile γ-deprotonation to give propargyl copper­(I) species and thus react with N -Boc aldimines with α-selectivity (Scheme c). To our joy, the reaction indeed occurred.…”
Section: Introductionmentioning
confidence: 99%
“…2). 130 In another report on Mannich-type reaction of aldimines and cyclopropanols, Ph-BPE was used but no enantioselectivity was detected. 131…”
Section: Reactionsmentioning
confidence: 99%
“…At present, the main types of directing groups are as follows: 2-oxazolidone (A) [29][30][31][32][33][34][35][36][37][38][39][40], tetrahydropyrrole 2,5-dione (B) [41][42][43], pyrazole or 3,5-dimethylpyrazole (C or D) [44][45][46][47][48][49][50][51][52][53][54][55][56], and 8-aminoquinoline (E) [57][58][59][60][61][62][63][64][65]. They coordinate with metals to form stable five-or six-membered ring complexes that control the stereoselectivity of the reaction through a specific chiral environment (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%